THE OUTCOMES OF THE ROMANIAN EDUCATIONAL SYSTEM AND ECONOMIC INDICATORS - JIVAN, Alexandru; ȘIPOȘ, Ciprian Alexandru; WEISZ, Janeta (Studia Universitatis Babeș-Bolyai Oeconomica, 2017)
https://doi.org/10.1515/subboec-2017-0008 The paper highlights some important correlations between the outcomes of the Romanian educational system and certain key indicators concerning the Romanian economy. The indicators are selected on the basis of the logic correlations and considering the limits of available data. The time-lag models were used because the macroeconomic effects of the factorial indicators considered as determinants on dependent variables cannot be usually detected in the same year. The results allowed interesting discussions concerning the Romanian education system and its funding-related evolutions in the last decade. JEL classification: I21, I28, O15